From iumk to bpom: feasibility analysis of minie cake business based on legal and financial aspects - Nandika S. Ayu; Amanda Miranti; Hikmahijriya R. Iskandar; Surahman Surahman; Rahmawati I. Wibowo (Institute of Computer Science (IOCS), 2025)
This study evaluates the business feasibility of Minie Cake by reviewing four main aspects, namely market finance, human resources, and legal aspects. A mixed approach was used through observation, interviews, and financial data analysis with NVP, IRR, and BEP indicators. The results show that the Minie Cake business is classified as feasible and profitable, with a positive NPV of IDR 8,707,917,836, an IRR of 2297%, and a BEP of only 258 units per year. In addition, compliance with business licenses, ranging from IUMK to BPOM certification, increases consumer confidence and business sustainability. This study concludes that the combination of financial viability and legal compliance is a strong foundation for the long-term competitiveness of Indonesian MSME bakeries.